Ejector-based nanoparticle sampling from pressures down to 20 mbar. (June 2020) - Rosenberger, Thore; Neises, Julian; Kiesler, Dennis; Kruis, Frank Einar
Abstract: The application of standard online instrumentation, such as scanning mobility particle sizer (SMPS), centrifugal particle mass analyzer or aerosol particle mass analyzer (CPMA/APM), and electrical low-pressure impactor (ELPI+) to low-pressure processes is only possible with extensive modification of the devices and extensive calibrations. A low-pressure ejector is a suitable device to transfer aerosol nanoparticles from low-pressure regions to atmospheric pressure and allows the direct use of standard online instrumentation. In this work, a commercial low-pressure ejector is investigated in the pressure range from 20–180 mbar with fully-sintered and size-selected nanoparticles (15–80 nm) in order to extend the application range of online instruments to low-pressure processes and open up a new variety of analysis methods. Results are compared to our previous work which was limited to pressures above 120 mbar. A change in particle size during the measurements for fully-sintered silver particles was not observed. A particle dilution factor between 60–6500 was found. High particle losses in the ejector for large particle sizes are compensated by a lower gas dilution factor. Highlights: Vacuum ejector as a low-cost method to sample aerosol from low pressure environments. Continuous sampling from 20–180 mbar inlet pressure and transfer to atmospheric pressure. Determination of the ejector's transfer characteristic for quantitative measurements. Particle losses in critical orifices of different dimensions as function of pressure.